A case series of cyclic vomiting syndrome in paediatric patients at a tertiary care hospital in Chennai, Tamil Nadu, India - Mittal, Ruchi R.; Ravichandran, Latha; Elayaraja, Elayaraja (International Journal of Contemporary Pediatrics, 2018)
Background: Cyclic vomiting syndrome is an increasingly recognized disorder with sudden, repeated episodes of severe nausea, vomiting, and physical exhaustion that occur with no apparent cause. It is more common in children than adults. However, we don’t often see a diagnosis of cyclic vomiting syndrome being made. Hereby we report 7 cases of cyclical vomiting. Methods: This is a retrospective study. Medical records of 5 years were review and consecutive paediatric patients discharged with a diagnosis of cyclic vomiting syndrome were identified, data collected and analysed. Results: Total of 7 cases were found, all of which were adolescents. The mean age was 13.28. 57.14% (4) were females and 42.86% (3) were boys. 42.86% (3) presented with complications. 14.28% (1) had an association with menstrual cycles and 14.28% (1) had an association with psychological stress. Conclusions: Cyclic vomiting syndrome should be kept in mind when a child presents with multiple episodes of vomiting, especially when repeated admissions have been made for the same. Early diagnosis and treatment can improve the quality of life.